Civil war and intrastate armed conflict changing dynamics in international perspective - DeRouen, Karl R. 1962-; Newman, Edward 1970-; Bellamy, Paul (Cambridge Cambridge University Press, 2025)
An examination of civil wars and intrastate armed conflicts underpinned by recent research, case studies, and detailed data. Using themes and accessible language, the textbook explores the causes, nature, and impact of violent civil conflict, and explains the main debates and methodologies which define the field
Introduction-- Debates and approaches in researching and studying civil war -- Impact of civil war and intrastate conflict -- Causes of civil war -- Natural resources and intrastate conflict -- Internationalized intrastate conflict-- Insurgency, rebel governance and counterinsurgency-- Atrocities in civil war -- Termination of civil war and post-conflict challenges-- International intervention, peacekeeping and peacebuilding-- Terrorism and intrastate conflict -- Conclusion: Policy implications for conflict resolution and peacebuilding-- Bibiliogrpahy.
Includes bibliographical references (pages [446]-513) and index.
Keywords: Civil war; International relations; Peace-building.